PERKEMBANGAN PONDOK PESANTREN AL-FATAH LAHAT DALAM BINGKAI SEJARAH 2007-2015 - Hafidhuddin, Hafidhuddin; Syahputra, Muhammad Candra (JURNAL ISLAM NUSANTARA, 2021)
Pesantren as the oldest Islamic educational institution in the archipelago is a place for the regeneration of ulama carried out by propagators of Islam to the indigenous population. Pesantren from its inception until now has been able to survive even though in its long journey it has faced many dynamics of changing times. The PesantrenÂ  Al-Fatah Lahat is an Islamic boarding school located in Lahat Regency, South Sumatra Province, founded by Kyai H. Ramlan Fauzi bin H. Hasanuddin bin H. Husein bin Delames bin Reseh bin Rijal Penghulu bin Magdum on December 6, 2007 M., to coincide with the 26th Dzul-qa'dah 1428 H. This article is the first article to examine the development and teaching of the Pesantren Al-Fatah Lahat, which is a historical analysis from 2007 to 2015. This pesantren is located in the middle of a heterogeneous urban community life and is a pesantren with a comprehensive typology that combines traditional and modern teaching systems. The method used in this research is the historical method. At first (2007) Pesantren Al-Fatah Lahat prioritized the Qurâ€™an with all aspects of its knowledge. Then established a formal education level MTs. The development of Al-Fatah in 2011 began to be recognized by MTs Al-Fatah around the Lahat district over time until 2015 this pesantren was not only students from the Lahat area, there were also from various areas outside the Lahat district.